Antibacterial and antifouling polymer brushes incorporating antimicrobial peptide - Glinel, Karine; Jonas, Alain M; Jouenne, Thierry; Leprince, Jérôme; Galas, Ludovic; Huck, Wilhelm T S (Bioconjugate chemistry, 2009)
Surface-initiated atom transfer radical polymerization (ATRP) has been used to prepare antifouling copolymer brushes based on 2-(2-methoxyethoxy)ethyl methacrylate (MEO(2)MA) and hydroxyl-terminated oligo(ethylene glycol) methacrylate (HOEGMA). The amount of hydroxyl reactive groups incorporated into the brushes was varied by changing the composition of the monomer mixture. These coatings were subsequently functionalized by a natural antibacterial peptide, magainin I, via an oriented chemical grafting on hydroxyl groups, which maintains the activity of the peptide. The antibacterial activity of the functionalized brushes was successfully tested against two different strains of gram-positive bacteria.